Pencegahan Resiko HIV/AIDS pada Kelompok Rentan Remaja di SMKN 1 Ciamis - Rosmiati; Nur Hidayat; Adi Nurapandi; Nisa Nuraeni; Fadila Nurizakiah; Amelia Puspita Sukmana; Irena Nurulazmi; Asep Aziz; Reval Al Attaya; Susi Lestari (Yayasan Inspirasi El Burhani, 2022)
Introduction: HIV is a virus that can be caused by the Acquired Immunodeficiency Syndrome (AIDS). The HIV virus that is increasingly spreading or severe will lead to and cause AIDS. White blood cells are attacked by the HIV virus and cause damage to a person's immune system. This virus spreads rapidly and the African continent is its root and origin. No one has ever found a medicine to cure someone from this disease. A person's change from children to adults is definitely physical, attitude, and others experience changes. HIV/AIDS can arise if a person's changes are not appropriate. Objective: Health education regarding the prevention of HIV/AIDS can help educate the students of SMKN 1 Ciamis on how to keep the spread of HIV/AIDS and avoid various HIV/AIDS viruses. Method: Health education research is used in the HIV/AIDS risk prevention education method in the Adolescent Range. This health education was conducted with 36 students at SMKN 1 Ciamis, Ciamis Regency, with 15 respondents as respondents. Result: Results of health education on HIV/AIDS risk prevention in adolescents at SMKN 1 Ciamis. There are still students who don't seem to understand about the spread of HIV/AIDS, even their concern for HIV/AIDS is still very porly understood. This will actually cause harm to a group of teenagers and their surroundings, for example promiscuity in adolescence, bringing negative sources to adolescents, causing the spread of HIV/AIDS. Conclussion: Results of health education on HIV/AIDS risk prevention in adolescents at SMKN 1 Ciamis. Previously given counseling on HIV/AIDS prevention, there were students who did not understand HIV/AIDS prevention, but after being given knowledge about definition of HIV/AIDS, HIV/AIDS prevention, reason HIV/AIDS, ways of transmitting HIV/AIDS, it showed that students understood little the importance of preventing HIV/AIDS.